Analisis Kadar Abu Terhadap Kualitas Karbon Aktif Dari Kayu Pohon Karet - Situmeang, David Prinata; Sasmita, Aryo; HS, Edward (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Activated carbon materials with highly developed surface area are widely use dinnumerous fields, such as the separation and purification of liquids and gases in many areas of human and industrial applications, protection from toxic substances, solvent recovery and decolorizing, catalyst support, supercapacitors, electrodes, gas storage processes and biomedical engineering. This study aims to utilize rubberwood as raw material for making activated carbon. Activated carbon was prepared by carbonization process at 500°C for 1 hours using 10% ZnCl2 activator and sieving with a filter size of 200 mesh. The activated carbon product is then tested using proximate analysis. The results of the proximate analysis show that activated carbon has met SNI 06-3730-1995 with a ash content of 8,2%. Keywords: Activation, Activated carbon, Rubberwood